Fibroepithelial Lesions of the Breast: Key Imaging and Pathologic Features. (15th April 2017) - Desouches, Stephane; Saettele, Megan; Adler, Kalie; Khalighi, Mazdak; Winkler, Nicole
Abstract : Fibroepithelial lesions are encountered commonly in a breast imaging practice and may be detected clinically or by imaging. They represent a spectrum of solid breast masses ranging from benign fibroadenomas to malignant phyllodes tumors and are differentiated pathologically by varying degrees of stromal and glandular elements. Clinical history and breast examination, mammography, breast ultrasound, and MRI may further help with characterization of the breast masses, but none of these procedures can unequivocally differentiate benign from malignant lesions. Depending on imaging features, work-up of the breast mass may include short-term follow-up versus core needle biopsy and/or possibly surgical excision. Radiologic and pathologic correlation guides further management.